ILC2s amplify PD-1 blockade by activating tissue-specific cancer immunity - Moral, John Alec; Leung, Joanne; Rojas, Luis A.; Ruan, Jennifer; Zhao, Julia; Sethna, Zachary; Ramnarain, Anita; Gasmi, Billel; Gururajan, Murali; Redmond, David; Askan, Gokce; Bhanot, Umesh; et al. (Nature (London), 2020)
Group 2 innate lymphoid cells (ILC2s) regulate inflammation and immunity in mammalian tissues 1 , 2 . Although ILC2s are found in cancers of these tissues 3 , their roles in cancer immunity and immunotherapy are unclear. Here we show that ILC2s infiltrate pancreatic ductal adenocarcinomas (PDACs) to activate tissue-specific tumour immunity. Interleukin-33 (IL33) activates tumour ILC2s (TILC2s) and CD8 + T cells in orthotopic pancreatic tumours but not heterotopic skin tumours in mice to restrict pancreas-specific tumour growth. Resting and activated TILC2s express the inhibitory checkpoint receptor PD-1. Antibody-mediated PD-1 blockade relieves ILC2 cell-intrinsic PD-1 inhibition to expand TILC2s, augment anti-tumour immunity, and enhance tumour control, identifying activated TILC2s as targets of anti-PD-1 immunotherapy. Finally, both PD-1 + TILC2s and PD-1 + T cells are present in most human PDACs. Our results identify ILC2s as anti-cancer immune cells for PDAC immunotherapy. More broadly, ILC2s emerge as tissue-specific enhancers of cancer immunity that amplify the efficacy of anti-PD-1 immunotherapy. As ILC2s and T cells co-exist in human cancers and share stimulatory and inhibitory pathways, immunotherapeutic strategies to collectively target anti-cancer ILC2s and T cells may be broadly applicable. Tumour-infiltrating group 2 innate lymphoid cells prime CD8 + T cells and amplify the anti-tumour effects of PD-1 blockade in pancreatic ductal adenocarcinoma.